Performance of participatory and non-participatory farmers of integrated crop management project at Pirganj upazila under Thakurgaon district (Journal of the Bangladesh Agricultural University, 2010)
This study examines technical efficiency between Participatory & Non- Participatory farmers under Integrated Crop Management project (ICM) in the north-west region of Bangladesh. Sixty farmers of which 30 participatory & 30 non-participatory were selected following stratified random sampling technique from four villages under pirganj upazila in Thakurgaon district. ICM project participatory farmers received higher net returns than the non-participatory farmers from selected crop production. Participatory farmers were technically more efficient than non- participatory farmers. Getting membership status of non- participatory farmers was suggested to be an important factor in removing technical inefficiency. Keywords: Technical efficiency; Participatory; Non-participatory DOI: 10.3329/jbau.v7i2.4734 J. Bangladesh Agril. Univ. 7(2): 273-280, 2009